Validation of the Short‐Form Survivor Unmet Needs Survey in older patients with myeloma - Pereira, M.Graça (2022)
Background: Multiple myeloma (MM) affects mainly the older population and is the second most prevalent haematologic cancer. MM patients’ unmet needs are diverse, arise at different stages, and are associated with greater psychological distress. This study examined the psychometric properties of the Short-Form Survivor Unmet Needs Survey (SF-SUNS) in Portuguese MM patients. Methods: This cross-sectional study included 213 MM patients. The internal consistency of the scale was analyzed with Cronbach’s α. Principal component analysis and confirmatory factor analysis were used to assess construct validity. Convergent validity was examined by using correlations with quality of life, satisfaction with social support, and psychological morbidity. Multiple regression analyses were conducted to explore the contribution of sociodemographic and clinical variables to unmet needs. Results: The Portuguese SF-SUNS’s factor structure follows the original’s structure, although it includes fewer items. For each domain, Cronbach’s α was ≤0.70, the minimum acceptable criterion. For construct validity, only unmet relationship and emotional needs had significant correlations (r ≥ 0.40)—specifically negative associations with quality of life and social support and positive associations with psychological morbidity. Regarding patient variables and SF-SUNS results, only cancer stage contributed significantly to unmet information needs, with patients at stage I reporting more needs than patients at stage III. Conclusions: The SF-SUNS represents a valid and reliable tool to assess unmet needs among Portuguese MM patients. It may be useful in designing and monitoring interventions to improve well-being in cancer survivors.